Managing Recurrent Clozapine-Induced Constipation in a Patient with Resistant Schizophrenia - Tomulescu, Silviu; Uittenhove, Kim; Boukakiou, Reda (Case Reports in Psychiatry, 2021)
Clozapine is an effective antipsychotic for the treatment of resistant schizophrenia. However, clozapine can lead to serious side effects. One of the most common side effects is constipation and in rare cases ileus, which is associated with a considerable case fatality rate. Our patient exhibited repeated episodes of ileus while being treated with clozapine. We adapted the treatment of the patient in several ways to manage these severe side effects. First, we reduced clozapine dosage by opting for an augmentation strategy of clozapine through paliperidone. Then, we added linaclotide as a nonconventional laxative. We further adapted treatment after the occurrence of a volvulus prompting surgical intervention which revealed a malformation of the intestines’ peritoneal attachment. A gastrostomy to facilitate the treatment of any further episode was performed and bethanechol was introduced alongside linaclotide. Follow-up revealed the efficacy of our strategy involving the use of linaclotide in managing the side effects of clozapine in this patient.